Rectum Carcinoid Tumors - Viola Malet, Marcelo; Amorín, Rosario; Barreiro, Claudia (Cirugía del Uruguay, 2006)
Carcinoid tumors are amorphologically defined 6/ass of intestine tumors which occur only rarely and are /ess aggressive than intestine aden9carcinomas. Their endocrinous natura was recognised only years after they had become a known entity. The immediat consequence of being rare is that few surgeons ever come across patients which suffer from this condition. In 1980 the WHO defined them as diffused tumors of the neuroendocrinous system or benign neoplasms with better prognosis than otther carcinomas; they are characterized by their particular/y s/ow growth rate, argentaphin affinity, immunihistochemical reaction with regard to neuronal specific labels and with the capacity of expressing various different peptides and biogenic amines